1980
DOI: 10.1104/pp.65.4.578
|View full text |Cite
|
Sign up to set email alerts
|

Vein Loading in Seedlings of Phaseolus vulgaris Exposed to Excess Cobalt, Nickel, and Zinc

Abstract: Vein loading in unifoliate leaves of white bean seedlings exposed to excess Co2", Ni2", or Zn2" for 1 to 4 days was studied by incubating leaf discs in I14Clsucrose. The discs from plants exposed to metal exhibited an increased total uptake of radiosucrose but reduced vein loading. Differences between treatments due to infiltration of disc margins were eliminated by analyzing 7-millimeter discs cut from the center of incubated 14-millimeter discs. Uptake of radiosucrose was greater particularly in discs from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 5 publications
2
22
2
1
Order By: Relevance
“…Such findings are similar to those reported for Spirodela polyrhiza (Appenroth et al, 2003). According to Rauser and Samarakon (1980), Cr reduces carbohydrate flow in the phloem, an effect that may be mediated by the inhibition of transport of sucrose from the inside to the outside of the chloroplast envelope. Poschenrider et al (1991) suggested that this phenomenon might be associated with an increase of 11010-p.2 ICHMET 2012 biologically active iron in solution.…”
Section: Resultssupporting
confidence: 89%
“…Such findings are similar to those reported for Spirodela polyrhiza (Appenroth et al, 2003). According to Rauser and Samarakon (1980), Cr reduces carbohydrate flow in the phloem, an effect that may be mediated by the inhibition of transport of sucrose from the inside to the outside of the chloroplast envelope. Poschenrider et al (1991) suggested that this phenomenon might be associated with an increase of 11010-p.2 ICHMET 2012 biologically active iron in solution.…”
Section: Resultssupporting
confidence: 89%
“…However, the effects of Cd on chloroplast structure differ from those induced by other heavy metals. Heavy metals were shown to induce starch accumulation, probably by inhibition of vein loading [48][49][50]. In the present study, the absence of starch accumulation in chloroplast stroma may be explained by the inhibition of photosynthesis by Cd [51][52][53].…”
Section: Discussionmentioning
confidence: 62%
“…The densitometric method for quantifying the contrast between mesophyll and veins (Rauser and Samarkoon 1980) was not appropriate for the highest-order veins: the background labelling (radioactivity in the mesophyll) turned out to be too high. Instead, we developed a by-eye estimation procedure which was carried out independently by three persons.…”
Section: Discussionmentioning
confidence: 97%